2022
DOI: 10.1108/jfm-05-2021-0051
|View full text |Cite
|
Sign up to set email alerts
|

New ways of working scale development and psychometric properties: validation in higher education institutions in the GCC countries

Abstract: Purpose This study aims to develop a scale for new ways of working (NWW) in higher education institutions in the Gulf Cooperation Council (GCC) countries. The study also intends to validate the psychometric properties of the developed scale. Design/methodology/approach This study targeted the academic staff of universities in the GCC region. Out of the 1,200 questionnaires distributed, only 1,016 questionnaires represented valid responses. Because there was not a unified theory for NWW, the authors developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…This means that the NWW practices scale has high reliability and discriminant validity. This aligns with the results of previous studies (Almahamid et al, 2021;Gerards et al, 2018Gerards et al, , 2021 that considered NWW as a five-factorial variable.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This means that the NWW practices scale has high reliability and discriminant validity. This aligns with the results of previous studies (Almahamid et al, 2021;Gerards et al, 2018Gerards et al, , 2021 that considered NWW as a five-factorial variable.…”
Section: Discussionsupporting
confidence: 91%
“…Contrasting previous studies, no significant direct relationship was found between advanced ICT communications (β = .12, P > .05) and IWB. This result was unexpected, counterproductive and contrary to the results of prior studies (Almahamid et al, 2021;Blok et al, 2012;Demerouti et al, 2014;Kingma, 2019;ten Brummelhuis et al, 2012), which asserted the importance of using advanced ICT-based communications tools to perform daily work tasks. This result could be attributed to two reasons.…”
Section: Gerards Et Al (2021)contrasting
confidence: 92%
See 3 more Smart Citations